2020
DOI: 10.1111/tpj.15042
|View full text |Cite
|
Sign up to set email alerts
|

Single‐parent expression drives dynamic gene expression complementation in maize hybrids

Abstract: SUMMARYSingle‐parent expression (SPE) is defined as gene expression in only one of the two parents. SPE can arise from differential expression between parental alleles, termed non‐presence/absence (non‐PAV) SPE, or from the physical absence of a gene in one parent, termed PAV SPE. We used transcriptome data of diverse Zea mays (maize) inbreds and hybrids, including 401 samples from five different tissues, to test for differences between these types of SPE genes. Although commonly observed, SPE is highly genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 81 publications
(116 reference statements)
3
12
0
Order By: Relevance
“…The dominance model, also known as the complementation model, describes the concept that deleterious alleles of different genes in both inbred lines are complemented in the F 1 -hybrid by beneficial alleles, which results in its superior phenotypic performance ( Jones, 1917 ). Recently, SPE complementation was demonstrated in genetically diverse maize genotypes along different stages of primary root development grown under controlled environmental conditions ( Baldauf et al, 2018 ) and in aboveground tissues ( Li et al, 2021 ). It was shown that non-syntenic genes were the driving force of gene expression complementation in hybrids ( Paschold et al, 2014 ; Marcon et al, 2017 ; Baldauf et al, 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominance model, also known as the complementation model, describes the concept that deleterious alleles of different genes in both inbred lines are complemented in the F 1 -hybrid by beneficial alleles, which results in its superior phenotypic performance ( Jones, 1917 ). Recently, SPE complementation was demonstrated in genetically diverse maize genotypes along different stages of primary root development grown under controlled environmental conditions ( Baldauf et al, 2018 ) and in aboveground tissues ( Li et al, 2021 ). It was shown that non-syntenic genes were the driving force of gene expression complementation in hybrids ( Paschold et al, 2014 ; Marcon et al, 2017 ; Baldauf et al, 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SPE complementation was demonstrated in genetically diverse maize genotypes along different stages of primary root development grown under controlled environmental conditions ( Baldauf et al, 2018 ) and in aboveground tissues ( Li et al, 2021 ). It was shown that non-syntenic genes were the driving force of gene expression complementation in hybrids ( Paschold et al, 2014 ; Marcon et al, 2017 ; Baldauf et al, 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, function complementation between dominant superior loci in hybrids has been reported to trigger heterosis in crops (5,6). In addition, single-parent expression has been found to be a general mechanism driving expression complementation in some hybrids (7)(8)(9). However, despite these findings, concurrent complementation of gene expression and biological function in a hybrid has rarely been reported, and it has remained a challenge to associate the genetic complementation in a hybrid with its heterotic phenotypes.…”
mentioning
confidence: 99%
“…Further, the genome assemblies of the six parents with annotation from a five-tissue transcriptome atlas (Li et al 2021; Bornowski et al 2021) are available for study, which increases the variety of opportunities for maize researchers. This population could be used to assay the effect of the alleles present within the population on combining ability, adaptation, genotype by environment interaction, stability, and provide a new paradigm for studying traditional and genomic selection.…”
Section: Discussionmentioning
confidence: 99%